Genome-Based Comparison of Cyclic Di-GMP Signaling in Pathogenic and Commensal Escherichia coli Strains - Povolotsky, Tatyana L. (J Bacteriol, 2015)
The ubiquitous bacterial second messenger cyclic di-GMP (c-di-GMP) has recently become prominent as a trigger for biofilm formation in many bacteria. It is generated by diguanylate cyclases (DGCs; with GGDEF domains) and degraded by specific phosphodiesterases (PDEs; containing either EAL or HD-GYP domains). Most bacterial species contain multiples of these proteins with some having specific functions that are based on direct molecular interactions in addition to their enzymatic activities. Escherichia coli K-12 laboratory strains feature 29 genes encoding GGDEF and/or EAL domains, resulting in a set of 12 DGCs, 13 PDEs, and four enzymatically inactive “degenerate” proteins that act by direct macromolecular interactions. We present here a comparative analysis of GGDEF/EAL domain-encoding genes in 61 genomes of pathogenic, commensal, and probiotic E. coli strains (including enteric pathogens such as enteroaggregative, enterohemorrhagic, enteropathogenic, enterotoxigenic, and adherent and invasive Escherichia coli and the 2011 German outbreak O104:H4 strain, as well as extraintestinal pathogenic E. coli, such as uropathogenic and meningitis-associated E. coli). We describe additional genes for two membrane-associated DGCs (DgcX and DgcY) and four PDEs (the membrane-associated PdeT, as well as the EAL domain-only proteins PdeW, PdeX, and PdeY), thus showing the pangenome of E. coli to contain at least 35 GGDEF/EAL domain proteins. A core set of only eight proteins is absolutely conserved in all 61 strains: DgcC (YaiC), DgcI (YliF), PdeB (YlaB), PdeH (YhjH), PdeK (YhjK), PdeN (Rtn), and the degenerate proteins CsrD and CdgI (YeaI). In all other GGDEF/EAL domain genes, diverse point and frameshift mutations, as well as small or large deletions, were discovered in various strains. IMPORTANCE Our analysis reveals interesting trends in pathogenic Escherichia coli that could reflect different host cell adherence mechanisms. These may either benefit from or be counteracted by the c-di-GMP-stimulated production of amyloid curli fibers and cellulose. Thus, EAEC, which adhere in a “stacked brick” biofilm mode, have a potential for high c-di-GMP accumulation due to DgcX, a strongly expressed additional DGC. In contrast, EHEC and UPEC, which use alternative adherence mechanisms, tend to have extra PDEs, suggesting that low cellular c-di-GMP levels are crucial for these strains under specific conditions. Overall, our study also indicates that GGDEF/EAL domain proteins evolve rapidly and thereby contribute to adaptation to host-specific and environmental niches of various types of E. coli.